METODE STUDI KASUS MENINGKATKAN HASIL BELAJAR SISWA PADA FUNGSI ALJABAR DI KELAS XI MIPA1 SMAN 1 KADUGEDE - Maman Maman (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The main objective of this research is to improve student learning outcomes, student activity in learning, and student responses to learning the concept of Algebraic Functions using the Case Study Method with a factual context. The research was conducted using the Classroom Action Research (CAR) approach with the John Elliot PTK model which consisted of 2 (two) cycles. Each cycle contained 4 (four) stages, namely planning, action, observation, and reflection. This research was conducted in class XI. MIPA1 SMA Negeri 1 Kadugede with a total of 37 students. This research is focused on the material of Algebraic Functions. Data collection techniques used were tests, worksheets, observation sheets, questionnaires, and student interviews. From the results of the study, in cycle II there was an increase in activity and student learning outcomes from cycle I namely. In cycle II, the average post-test score of 90.54 students was obtained and the percentage of completeness of student learning outcomes reached 100% of students achieving grades â‰¥70. And from the results of student questionnaires and the results of observations on learning using the case study method, there were very good responses from students. This proves that learning using the case study method has a positive impact on student learning outcomes in Algebraic Functions.